Do Clopidogrel Nonresponders Have an Increased Risk of Adverse Events during Supra-Aortal Angioplasty and Stenting?. (28th February 2012) - Koerner, Heiko; Derveaux, Christian; Alexandrou, Maria; Graeber, Stefan; Roth, Christian; Papanagiotou, Panagiotis; Eichler, Hermann; Reith, Wolfgang
Abstract : Objective . The aim of the present study was to correlate new periprocedural diffusion-weighted imaging (DWI) lesions during stenting of supra-aortal arteries with the level of platelet inhibition using point-of-care analysis. Background . Cardiological studies have shown that patients undergoing coronary PTA have a significantly elevated risk of severe thrombotic complications if patients show insufficient inhibition of platelet function. Methods . From August 2008 to June 2009, 44 patients with an indication of supra-aortal angioplasty and/or stenting were prospectively enrolled. Platelet reactivity was tested using a Multiplate device (Dynabyte). These patients underwent MRI before and after the intervention to determine the prevalence of new DWI lesions. The primary endpoint was the prevalence of DWI lesions; the secondary endpoint was clinical status until discharge from hospital. Results . There was no significant relationship between the primary endpoint and the degree of platelet function. Patients with high platelet reactivity showed the same amount of periprocedural complications as patients with sufficient inhibition of platelets. Conclusions . Clopidogrel did not have a protective effect on periprocedural complications, nor did it decrease the number of silent DWI lesions after the procedure. The predescribed strong relationship between high platelet reactivity and early post-procedural adverse events was not observed in our cohort.